"The Academic System for Studying Public Administration in the Kingdom of Saudi Arabia: A Comparative Study" - Alrasheed, Mishaal (The Arab Journal of Administration, 2022)
The study aims to identify the academic system for studying public administration in the Kingdom of Saudi Arabia and compare it with the United States of America. The comparative approach was followed by preparing the comparison card, which dealt with the similarities and differences about the academic system in the study of public administration in the Kingdom of Saudi Arabia and the United States of America. The study was applied to the academic system in teaching public administration in the Kingdom of Saudi Arabia and compared to the United States of America. The study showed the most important differences between the two universities in the teaching of public administration, the most prominent of which was that universities in the Kingdom of Saudi Arabia focus on the theoretical side of public administration, unlike universities in the United States of America, which focus on the student deepening in the specialization applied more than theoretically. The conditions for student admission to a master’s program differ in both countries, and doctoral programs in public administration in universities in the Kingdom of Saudi Arabia focus on teaching human resources management courses in the public sector, health management, and public financial management, while in the United States of America they focus on teaching The fields of environmental policy, international economic policy, decision sciences, science and technology, international security relations, risk assessment and policy for economic regulation, international development, governance, and decision-making. With the students’ needs, goals, and previous experiences, and providing financial support to public administration programs, provide them with academic expertise, cooperating with advanced universities, and trying to benefit from their experiences in teaching.